The Relationship Between Corporate Governance and CEO Compensation: Evidence From UK Listed Companies - Wu, Jieru (2020)
Executive compensation has been a hot topic over the past decades. More and more people find that soaring executive compensation may not cause a corresponding increase in firm performance. How to keep executive compensation at a reasonable level is a complicated problem for modern companies. The purpose of this paper is to examine the impact of corporate governance on Chief Executive Officers’ (CEO) compensation. Based on the data of 149 non-financial firms listed in the United Kingdom over the period from 2009 to 2018, this paper uses panel data analysis to investigate the relationships between CEO pay and corporate governance factors, including CEO duality, board structure and institutional ownership. The regression results suggest that CEO duality does not influence the level of cash-based CEO pay but positively affects equity-based CEO compensation. Both kinds of CEO compensation are positively correlated to board size. Institutional ownership and board independence have a positive impact on the level of CEO pay, which indicates that independent directors and institutional investors monitor executives actively and effectively. Remuneration committee size and board gender diversity do not influence the level of CEO pay. This paper also finds that, in addition to corporate governance factors, CEO pay is affected by firm performance, firm size and firm age. Companies with more assets 4 and better performance pay more compensation to their CEOs. Younger firms tend to pay less to their CEOs than older ones.